Characterization and in planta validation of a CHI4 chitinase from Cajanus platycarpus (Benth.) Maesen for its efficacy against pod borer, Helicoverpa armigera (Hübner). Issue 5 (27th January 2021) - Rathinam, Maniraj; Marimuthu, Sathish Kumar; Tyagi, Shaily; Kesiraju, Karthik; Alagiamanavalan, Lakshmi Prabha; Rao, Uma; Sreevathsa, Rohini
Abstract: BACKGROUND: Pigeonpea, Cajanus cajan is one of the economically important legume food crops and a major source of dietary proteins. Management of pod borer, Helicoverpa armigera has been prominent among crop improvement programs. Lack of resistance sources in the cultivated germplasm and crossing incompatibility with pod borer‐resistant wild relatives have prompted biotechnological interventions. Identification and exploitation of genes from pigeonpea wild relatives in host plant resistance towards the pod borer assumes pertinence. Dynamic transcriptome analysis of the wild relative vis a vis cultivated pigeonpea identified a CHI4 chitinase as one of the putative insect resistance genes. RESULTS: The study presents variations in important amino acids in CHI4 chitinases from C . cajan and its wild relative C. platycarpus . Comparative protein modeling and docking analysis of the two proteins demonstrated differences in substrate binding efficacy of the chitinase from C. platycarpus which resulted in a minimum binding energy of −8.7 kcal mol −1 . Furthermore, we successfully evaluated the insecticidal activity of the chitinase from C. platycarpus against H. armigera challenge through heterologous expression in tobacco. Molecular characterization of transgenic plants confirmed that their efficacy against H. armigera was a result of the integration of CHI4 from C. platycarpus . CONCLUSION: Docking analysis demonstrated effective substrate interaction as a possible reason for efficacy against pod borer in the chitinase from C. platycarpus . This was authenticated by successful overexpression and bioefficacy assessment against H. armigera in tobacco. The CHI4 gene from C. platycarpus can be useful in the mitigation of H. armegira in pigeonpea as well as in other crops. © 2021 Society of Chemical Industry Abstract : In this study, we focused primarily on the assessment of molecular variations between Cajanus cajan‐CHI4 and Cajanus platycarpus‐CHI4 in their structure and its extrapolation to efficient enzyme–substrate interaction through molecular docking. Further, efficacy of C. platycarpus‐CHI4 against Helicoverpa armigera was validated through heterologous expression in tobacco plants.